The effect of recombinant interleukin-2 on the variation of the cytokine balance in the patients with uterine myomas - I. N. Pyatakova; V. M. Zhenilo (Медицинский вестник Юга России, 2010)
Purpose: To develop an option for the anesthetic support of such surgical interventions with the use of human recombinant interleukin-2, which makes it possible to normalize the cytokine balance of the patients with uterine myomas during the surgical stress and in the early post-operative period.Materials and Methods: The cytokine balance was measured during the surgery and in the early post-operative period in patients with uterine myomas operated on with total intravenous anesthesia and artificial ventilation of the lungs.Results: Based on a solid-phase immunoenzymatic test, it was found that at all stages of examination of that group of patients there was an imbalance between the pro-inflammatory and the anti-inflammatory links of the cytokine regulation of the course of the adaptation processes.